Social Media Marketing Strategies In The Global Halal Industry - Muhammad Faisal Yul Zamrudi; Bae Il-Hyun (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The global halal market has evolved tremendously over the years owing to increased demand for their goods, technology, and use of digital mediums. The current research has been conducted to evaluate the impact of social media strategies across the global halal industry. For this purpose, qualitative data collection via secondary research through systematic review via Prisma analysis has been undertaken. The research findings highlight the importance of social media marketing strategies in increasing customer engagement, competencies, growth, and competitive advantage. It also speaks of challenges of such strategies which need to be overcome for ensuring sustainable business operations.